1. The problem statement, all variables and given/known data if x1 and x2 are solutions to 1) x² + x + 1 = 0, then 2) y1 = ax1 + x2 and 3) y2 = x1 + ax2 are solutions to which quadratic equation? 2. Relevant equations ax² + bx + c = 0 x1∕2 = (−b ± √(b² - 4ac))/2a 3. The attempt at a solution Well, firstly i solved for x1 and x2 getting: x1 = (−1 + √(-3))/2 x2 = (−1 - √(-3))/2 I now have in mind to replace the x1 and x2 in equations 2) and 3), and after i simplify best i can to find the equation by means of following formula: (y - y1)(y - y2) Will this yield the solution, and is there a simpler way of doing this? The simplification alone is a hard task letalone the multiplication that comes afterwards.